The incidence and follow-up of isolated ventricular septal defect in newborns by echocardiographic screening - Ekici, Filiz; Tutar, Ercan; Atalay, Semra; Arsan, Saadet; Özçelik, Nazire (The Turkish Journal of Pediatrics, 2008)
The aim of this study was to evaluate the incidence and spontaneous closure rate of ventricular septal defects in a randomly selected newborn population, using color flow Doppler echocardiographic screening. Color flow Doppler echocardiographic screening was performed in 1075 neonates within the first 72 hours of life. We also followed-up patients with ventricular septal defect for a year to detect spontaneous closure rate and its timing. The incidences of ventricular septal defect in all neonates, preterm neonates and term neonates were found as 47.4/1,000, 56/1,000 and 46.3/1,000 live births, respectively. All patients with ventricular septal defect except one were asymptomatic. Forty-six cases had a trabecular and five cases had perimembranous ventricular septal defect. With the exception of one case, all had a small ventricular septal defect (< or =3 mm). Spontaneous closure was observed in 88.6% of ventricular septal defects within the first year. Closure rate was found as 100% for preterm infants and 87.8% for term infants (p>0.05). The incidence of ventricular septal defect was considerably high in neonates when routine color flow Doppler echocardiographic examination was performed. Despite increased incidence of ventricular septal defect, spontaneous closure rate was remarkably high within the first year of life. These defects may result from delayed physiologic development and have fairly good prognosis.